The need of social-pedagogical support of the process of inculturation pupils -repatriates in light of the national idea «Mangilik yel» (Journal of Philosophy Culture and Political Science, 2018)
The article considers the actual social problem of modern Kazakhstan – the process of inculturation of pupils-returnees. According to the author, the process of entering immigrants in new socio-cultural space, the comprehension of the personality of its cultural identity, all this requires a social-pedagogical support of the process of inculturation of immigrants. In the author’s view, inculturation is a kind of fusion with the native culture, the emergence of educated. The article explains the lengthy and complex process that involves learning the traditions and norms of behavior in their own culture. Based on the analysis of sources, the author convinces us that inculturation includes the formation of basic human skills, including communication with other people, monitoring own behavior and emotions, basic needs,  ... evaluation of various phenomena of the surrounding world, etc. According to researchers, they agree with the author, as a result of inculturation appears emotional, behavioral and even intellectual man’s resemblance to other members of the culture and the contrast of other cultures. However, it is noted the need of socio-pedagogical support of this process in terms of schooling, since children are faced with challenges: disadaptation, poor language skills and lack of understanding from peers.Key words: social-cultural space, enculturation, acculturation, socialization, repatriation, repatriate, oralman, cultural identity, cultural transmission, social-pedagogical support.